Granzyme B-based cytolytic fusion protein targeting EpCAM specifically kills triple negative breast cancer cells in vitro and inhibits tumor growth in a subcutaneous mouse tumor model. Issue 2 (28th March 2016) - Amoury, Manal; Kolberg, Katharina; Pham, Anh-Tuan; Hristodorov, Dmitrij; Mladenov, Radoslav; Di Fiore, Stefano; Helfrich, Wijnand; Kiessling, Fabian; Fischer, Rainer; Pardo, Alessa; Thepen, Theophilus; Hussain, Ahmad F.; et al.
Abstract: Triple-negative breast cancer (TNBC) is associated with poor prognosis and high prevalence among young premenopausal women. Unlike in other breast cancer subtypes, no targeted therapy is currently available. Overexpression of epithelial cell adhesion molecule (EpCAM) in 60% of TNBC tumors correlates with poorer prognosis and is associated with cancer stem cell phenotype. Thus, selective elimination of EpCAM + TNBC tumor cells is of clinical importance. Therefore, we constructed a fully human targeted cytolytic fusion protein, designated GbR201K-αEpCAM(scFv), in which an EpCAM-selective single-chain antibody fragment (scFv) is genetically fused to a granzyme B (Gb) mutant with reduced sensitivity to its natural inhibitor serpin B9. In vitro studies confirmed its specific binding, internalization and cytotoxicity toward a panel of EpCAM-expressing TNBC cells. Biodistribution kinetics and tumor-targeting efficacy using MDA-MB-468 cells in a human TNBC xenograft model in mice revealed selective accumulation of GbR201K-αEpCAM(scFv) in the tumors after i.v . injection. Moreover, treatment of tumor-bearing mice demonstrated a prominent inhibition of tumor growth of up to 50 % in this proof-of-concept study. Taken together, our results indicate that GbR201K-αEpCAM(scFv) is a promising novel targeted therapeutic for the treatment of TNBC.